Aplikasi Pengenalan Plat Nomor Kendaraan Mahasiswa Di Universitas Riau - Noprizal, Noprizal; Candra, Feri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Vehicle license plate recognition application has been found in shopping centers, university, and other agency buildings with various methods of recognition. Some examples of methods used such as digital image processing techniques, neural networks and so forth. This study makes an application for the introduction of license plates, especially for student vehicle license plates in the university area. This application is developed with Digital Image Processing Methods and Artificial Neural Networks.In this study, 900 training data are used, taken from 200 photo vehicle number plates, to train 36 characters that contain 26 alphabets and 10 decimal numbers. The training data is used to test 30 photos of vehicle license plates. Plate photos used as training and testing data are the Indonesian standard with black and white plates. Artificial Neural Network used to recognize vehicle license plate by using the BPNN method with parameters Epoch 1000, Hidden layer1 with node 60, Hidden layer2 with node 55, Goal 0.001.The final conclusion of this Study shows that the use of Artificial Neural Network BPNN method is very good, with the best testing accuracy obtained, namely 98% and 1.25 error.Keywords: Digital Image Processing, Artificial Neural Networks,BPNN, Vehicle License Plate